Adherence to Palivizumab for Respiratory Syncytial Virus Prophylaxis in Romanian Infants - Andreea Calomfirescu-Avramescu; Adrian Ioan Toma; Claudia Mehedințu; Leonard Năstase; Vlad Dima (Vaccines)
Background: In 2022, Romania started an RSV immunoprophylaxis program with Palivizumab for infants at high risk: preterm infants born before 35 weeks of pregnancy, infants born with congenital heart defects, and infants with chronic lung disease. We evaluated treatment adherence from August 2022 to March 2024. Method: We monitored the increase in the number of patients enrolled in the program and the number of collaborating neonatologists, family doctors, and pediatricians. Adherence to all doses of Palivizumab in enrolled patients was assessed by telephone interviews. The factors contributing to reduced adherence were identified. Results: Between August 2022 and March 2024, 1903 patients and 233 specialists were enrolled, a steady increase in both cohorts. The percentage of patients that complete their full sequence of doses decreases along with the number of doses (99% for one dose, 73% for two doses, 47% for three doses, 35% for four doses, and 22% for five doses) due to several factors. Conclusions: The program remains highly regarded by both physicians and caregivers, demonstrating its effectiveness as a valuable resource for educating parents and facilitating monoclonal antibody administration as a prevention method for RSV.